225k views
3 votes
Please Help!!! What is the true solution to the equation below? 2log3(6x)-log3(4x)=2log3(x+2)

Please Help!!! What is the true solution to the equation below? 2log3(6x)-log3(4x-example-1
User John Roca
by
5.6k points

2 Answers

5 votes

Answer:

c on edge

Explanation:

User Joseph Lin
by
5.6k points
2 votes

Answer:

x = 1 and x = 4

Explanation:

A graph of the given equation, after rewriting to make the solutions be zeros of the function, shows the solutions to be x = 1 and x = 4.

You can take the antilog and solve the quadratic:

log3((6x)^2/(4x)) = log3((x+2)^2) . . . . consolidate the logs

9x = (x +2)^2 . . . . simplify and take the antilog

0 = x^2 -5x +4 . . . subtract 9x

0 = (x -4)(x -1) . . . . factor

Solutions are x = 1 and x = 4. (These values make the factors zero.)

Please Help!!! What is the true solution to the equation below? 2log3(6x)-log3(4x-example-1
User Xuan Tung Vu
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.